The complete mitochondrial genome of the hybrid Furong-crucian [Cyprinus capio Furong (♀) × Carassius auratus red var (♂)]. Issue 1 (1st January 2016) - Zou, Li; Wang, Jinlong; Zeng, Ming; Liu, Mingqiu; Wang, Dongwu; Wu, Yuanan; Li, Chuanwu; Jiang, Guomin; Liu, Li
Abstract: The complete mitochondrial genome of the hybrid of Cyprinus capio Furong (♀) × Carassius auratus red var. (♂) was characterized first in this study. The total length of the mitochondrial genome of Furong-crucian was identical to the female parent as 16, 581 bp, and the overall base composition was 31.87% A, 24.81% T, 27.56% C and 15.76% G, with a slight A + T bias. It contained 13 protein-coding genes (PCGs), 22 transfer RNA genes, 2 ribosomal RNA genes and 2 main non-coding regions (the control region and the origin of the light-strand replication). This study discovered the 99.3% sequence identity between the hybrid and its female parent, which confirmed the maternal inheritance pattern followed by the mitochondrial genome of the hybrid. However, the sequence alignment of mitochondrial genomes between the hybrid and its female parent revealed a total of 109 variable sites in 18 genes or regions, especially 32 sense mutations in 9 PCGs. The complete mitochondrial genome sequence of this hybrid Furong-crucian may provide an important dataset for further study in mitochondrial inheritance mechanism.